DAMPAK PENGEMBANGAN PARIWISATA TERHADAP EKONOMI DAN SOSIAL BUDAYA MASYARAKAT LOKAL DESA WISATA SASAK ENDE, LOMBOK - Surahman, Tantowi; Sudiarta, I Nyoman; Suwena, I Ketut (Jurnal Analisis Pariwisata, 2021)
Tourism development in an area will have an impact on the surrounding community. This study aims to determine the impact of tourism development on the economy and socio-culture of the local community in the Sasak village Ende, both positive and negative impacts. This research uses qualitative and quantitative data, with secondary and primary data sources, data collection through observation, documentation, questionnaires, in-depth interviews, and literature study. Using qualitative descriptive data analysis that describes the development of tourism in the Sasak Ende tourism village and its economic and socio-cultural impacts. The samples were determined using judgmental sampling which was distributed to 70 respondents with 14 statement items. Based on the results of data processing, the tourism development of the Sasa Ende tourism village has facilities and infrastructure as well as human resource development, tourism promotion, and very supportive event activities. Based on data processing, the positive impact of tourism development on the economy in a percentage range with an interpretation of 94.61%, while the negative impact is 82.42%. The positive impact of tourism development on socioculture is in the percentage range with an interpretation of 93.61% while the negative impact is 48.92%.